A Study on the Spatio-Temporal Evolution and Determinants of Green Development Efficiency in the Cultural Industry of the Yangtze River Economic Belt - Qin, Can; Zhang, Xuemei; Yang, Xiyue; Zhou, Rui; Cai, Yutong (Asia Pacific Economic and Management Review, 2026)
This study builds a super‑efficiency SBM framework that takes unintended outputs into consideration. Using the Dagum Gini index, Moran’s I statistic, and a principal component regression model, we evaluate the green development efficiency of the cultural sector across 11 provincial‑level units within the Yangtze River Economic Belt for the year 2023. The analysis uncovers both the spatial‑temporal dynamics and the driving forces behind efficiency. Our key findings are as follows. The overall green development efficiency of the cultural industry in this region remains fairly low, displaying a distinctive pattern: high efficiency in the lower reaches, weak technical capacity in the middle reaches, and limited scale in the upper reaches. Spatial differences mainly come from the gap between the lower and upper reaches, while significant internal variation exists within the upper reaches. Spatial clustering shows a clear “high‑high” and “low‑low” polarization with pronounced local agglomeration. The scale of the cultural industry acts as a positive driver, whereas energy intensity imposes a notable constraint. Against the background of the 15th Five‑Year Plan, this paper puts forward a coordinated approach that spans policy alignment, business model transformation, technological empowerment, and talent development. The aim is to foster sustained improvement in green development efficiency and contribute to high‑quality growth of the cultural industry.